PEMANFAATAN TEPUNG DAUN MENGKUDU (Morinda citrifolia) TERHADAP KUALITAS TELUR BURUNG PUYUH - Vivin Aminatu Solichah (Universitas Islam Balitar, 2023)
The experiment was conducted to determine influence of additing noni leaf flour on the quality of quail eggs. The materials used were 300 quail eggs 44 weeks old. The experiment used a Completely Randomized Design (CRD) with 4 treatments (0%, 1%, 2% and 3% of noni leaf flour in feed) and 5 replications. Parameters observed were haugh unit and egg shell thickness. The data were analysed using analysis of variance and continued with honest real difference test. The result showed that the addition of noni leaf flour in the feed ration had a significant effect (P>0,01) on the haugh unit and egg shell thickness. The conclusion of this experiment was the addition of noni leaf flour in feed ration had a significant effect on the quality of quail eggs. The P2 treatment (addition of 2% noni leaf flour) in quail feed showed the best results on egg quality that is haugh unit and egg shell thickness.